Introduction: 1821 and the Crooked Line to the Nation-State - Dialla, Ada A.; Kotsonis, Yanni D. (Historein, 2022)
This special issue is the outcome of a renewed interest in the study of 1821 and has its own history. It is the result of a series of workshops co-organised by New York University under the auspices of the Jordan Center for Advanced Study of Russia (New York) and the Research Centre for the Humanities (Athens). These workshops brought together historians and social scientists from different universities, and different national and academic environments, to discuss how the history of 1821 could be reconceptualised. 1821 was and still is, par excellence, an example of the political uses and abuses of history. So we seek to understand the revolution in terms of its own present. We titled these workshops as “1821: What Made it Greek and Revolutionary” because we aimed to view the events as if visiting them for the first time and reconsider them beyond the teleology which so much characterises any kind of revolutionary narrative.